2022
DOI: 10.11604/pamj.2022.42.180.34264
|View full text |Cite
|
Sign up to set email alerts
|

Role of plasma homocysteine levels and other associated factors with coronary artery disease among Palestinian patients in North Palestine: a case control study

Abstract: Introduction coronary artery disease (CAD) is one of the leading causes of death worldwide, only two thirds of cases can be explained by CAD´s classical risk factors. There is an increase in attention to homocysteine as a causal of CAD. In Palestine, CAD is more common than that in regional surrounding areas. Coronary artery disease is considered the leading cause of death in the West Bank, according to Palestinian Ministry of health annual reports. The study was conducted to determine the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The study by Chou and colleagues demonstrated that male subjects had higher homocysteine levels than female participants and the mean levels of plasma homocysteine were significantly higher in occluded coronary artery disease or in maintenance hemodialysis than in age-matched normal subjects [ 17 ]. Moreover, fasting plasma homocysteine levels were significantly elevated in adult men compared to women among coronary artery disease subjects including ACS patients [ 5 , 18 ]. In the present study, we found that the gender-associated difference also existed in ACS patients with normal renal function, with higher plasma concentration of homocysteine in adult men.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Chou and colleagues demonstrated that male subjects had higher homocysteine levels than female participants and the mean levels of plasma homocysteine were significantly higher in occluded coronary artery disease or in maintenance hemodialysis than in age-matched normal subjects [ 17 ]. Moreover, fasting plasma homocysteine levels were significantly elevated in adult men compared to women among coronary artery disease subjects including ACS patients [ 5 , 18 ]. In the present study, we found that the gender-associated difference also existed in ACS patients with normal renal function, with higher plasma concentration of homocysteine in adult men.…”
Section: Discussionmentioning
confidence: 99%